Critical making, critical niches: co-design for energy transitions and living labs in South Africa - Earl, Andrew Christopher (Stellenbosch : Stellenbosch University, 2025)
Earl, A. C. 2025. Critical Making, Critical Niches: Co-design for Energy Transitions and Living Labs in South Africa. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5cc2853a-79fd-406c-8400-cae7469ac0c7